Pengaruh Sistem Layanan Mobile Banking Terhadap Loyalitas Nasabah Bank Syariah Indonesia KC Sibolga - Agustina Sihombing (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine and analyze the influence of the mobile banking service system on customer loyalty at Bank Syariah indonesia KC Sibolga. The Population in this study are customers of Bank Syariah Indonesia KC Sibolga. The sample of this research is 338 customers. This research is a type of quantitative research using primary data. The sample and sampling in this study used a convenience sampling technique using non-probability sampling method. The analysis technique used is validity test, reliability test, simple linear regression analysis test, hypothesis test. The partial result show that there is an influence of the mobile banking service system on customers loyalty. The result of simultaneous study show that the mobile banking service system has a significant effect on customer loyalty of Bank Syariah Indonesia KC Sibolga.